Harnessing Bacteria for Sustainable Pest Management: A Biological Approach - , Shaana O M; , Nisha M S (Archives of Current Research International, 2025)
Microbial pest management in agricultural crops provides an environmentally sustainable alternative to chemical pesticides, aligning with the principles of Integrated Pest Management (IPM). This strategy relies on beneficial microorganisms, particularly entomopathogenic bacteria (EPB), which target and suppress insect pests through specific mechanisms such as toxin production, host colonization, and microbial symbiosis. Among EPBs, Bacillus thuringiensis (Bt) is the most widely used, producing Cry and Cyt toxins that disrupt insect gut function, leading to mortality. Other bacterial genera, including Photorhabdus, Xenorhabdus, Serratia, and Paenibacillus, also exhibit insecticidal properties and play crucial roles in microbial pest control. These bacteria are classified based on their pathogenic nature (obligate vs. facultative), spore production ability (spore-forming vs. non-spore-forming), and cell wall composition (Gram-positive vs. Gram-negative), which influence their effectiveness and application methods.The adoption of bacterial biopesticides within IPM frameworks reduces environmental contamination, mitigates pesticide resistance, and promotes ecological balance. Unlike chemical pesticides, bacterial control agents are highly specific to target pests, minimizing harm to non-target organisms such as pollinators and natural predators. This specificity is a key advantage, ensuring that beneficial insects and the broader ecosystem remain unharmed. Despite their promise, bacterial-based pest management faces challenges, including microbial persistence in the environment, formulation stability, and the feasibility of large-scale application. Continued research in microbial biotechnology, genomics, and improved formulation techniques is essential to overcome these limitations. Furthermore, regulatory support and public acceptance are critical for the successful integration of microbial biopesticides in modern agriculture. Advancements in this field will enhance sustainable agricultural practices, reduce dependence on chemical pesticides, and address the global challenge of food security while preserving environmental health and biodiversity.